Coal gasification for the coproduction of electricity and fertilizer - Kelly, D. A.; Nichols, D. E.; Faucett, H. L. (Tennessee Valley Authority, Muscle Shoals, AL (United States), 1992)
TVA is proposing to develop and commercially demonstrate the coproduction of electricity and fertilizer (urea) using integrated gasification/combined cycle (IGCC) technology. The coal-based coproduction demonstration project will show that the coproduction process can economically and environmentally enhance the production of both electric power and urea. As conceptualized, the proposed coproduction demonstration project facility would be designed for a nominal electrical capacity of about 250 megawatts (MW), Table I. During normal operation, the facility would produce about 150 MW of base-load electrical power and 1,000 tons per day of urea. Sulfur from the coal would be recovered as elemental sulfur. During peak power demand, the fertilizer capacity could be reduced or bypassed and the full 250 MW could be made available. This scheme would allow continuous operation of the gasifier at 100% of its rated capacity which would reduce the annual revenue requirements for power generation by permitting the production of fertilizer. As TVA's vision of this proposal matures (i.e., as consideration is given to alternative schemes, as TVA reviews its power demands, and as more detailed engineering estimates are developed), the nature and scope of cyclic-operation may be altered.